2004
DOI: 10.1103/physreva.69.063407
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic electronic dressing in laser-assisted electron-hydrogen elastic collisions

Abstract: We study the effects of the relativistic electronic dressing in laser-assisted electron-hydrogen atom elastic collisions. We begin by considering the case when no radiation is present. This is necessary in order to check the consistency of our calculations and we then carry out the calculations using the relativistic Dirac-Volkov states. It turns out that a simple formal analogy links the analytical expressions of the differential cross section without laser and the differential cross section in presence of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Using the Dirac-Volkov wave function that incorporates this anomaly [18], we found the analytical expression of the corresponding DCS. A spatial integral part that has been found in a previous work [21] remains the same for the study of this process. The various coefficients that intervene in the expression of S f i have been obtained using Reduce [22].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Using the Dirac-Volkov wave function that incorporates this anomaly [18], we found the analytical expression of the corresponding DCS. A spatial integral part that has been found in a previous work [21] remains the same for the study of this process. The various coefficients that intervene in the expression of S f i have been obtained using Reduce [22].…”
Section: Discussionsupporting
confidence: 59%
“…where the expression of H(∆ n ) has already been derived in a previous work [21],where ∆ n = |q f − q i − nk| is the momentum transfer with the net exchange of n photons.We have obtained for H(∆ n ) the following analytical expression :…”
Section: Theorymentioning
confidence: 99%
“…It is clear that the situation is different than in elastic collision [4], since we have no singularity in the case ∆ → 0.…”
Section: Integral Over Rmentioning
confidence: 90%
“…Payne et al [3] have studied the electron-impact excitation of the 5s −→ 5p resonance transition in rubidium by using a semirelativistic Breit-Pauli R-matrix with pseudo-states (close-coupling) approach. Attaourti et al [4] have investigated the exact analytical relativistic excitation 1S 1/2 −→ 1S 1/2 of atomic hydrogen by electron impact in the presence of a laser field. They have found that a simple formal analogy links the analytical expressions of the unpolarized differential cross--section (DCS) without laser and the unpolarized differential cross section in the presence of a laser field.…”
Section: Introductionmentioning
confidence: 99%
“…(26) of [1]. The corrections that we made allowed us to study other processes that were published in Physical Review A., namely an first article concerning the relativistic electronic dressing in laser assisted electron-hydrogen elastic collisions [10], another concerning the process of Mott scattering in an elliptically polarized laser field [11] as well as a third work dealing with the process of Mott scattering of polarized electrons in a strong laser field [12]. For the difficult process of ionization of atomic hydrogen by electron impact, we published an article concerning the importance of the relativistic electronic dressing in laser-assisted ionization of atomic hydrogen by electron impact [13].…”
Section: Resultsmentioning
confidence: 99%